Non-melancholic depressive symptoms are associated with above average fat mass index in the Helsinki birth cohort study - Eriksson Mia D; Eriksson Johan G; Korhonen Päivi; Salonen Minna K; Mikkola Tuija M; Kajantie Eero; Wasenius Niko S; von Bonsdorff Mikaela; Kautiainen Hannu; Laine Merja K (Nature Portfolio, 2022)
There is an existing link between two of the most common diseases, obesity and depression. These are both of great public health concern, but little is known about the relationships between the subtypes of these conditions. We hypothesized that non-melancholic depressive symptoms have a stronger relationship with both body composition (lean mass and fat mass) and dysfunctional glucose metabolism than melancholic depression. For this cross-sectional study 1510 participants from the Helsinki Birth Cohort Study had their body composition evaluated as lean mass and fat mass (Lean Mass Index [LMI, kg/m2] + Fat Mass Index [FMI kg/m2] = Body Mass Index). Participants were evaluated for depressive symptoms utilizing the Beck depression inventory, and had laboratory assessments including an oral glucose tolerance test. Higher than average FMI was associated with a higher percentage (mean [%], 95% CI) of participants scoring in the depressive range of the Beck depression inventory (20.2, 17.2-23.2) compared to those with low FMI (16.3, 13.8-18.9; p = 0.048) when adjusted for age, sex, education, and fasting plasma glucose concentration. Higher FMI was associated with a higher likelihood of having depressive symptoms (OR per 1-SD FMI = 1.37, 95% CI 1.13-1.65), whereas higher LMI was associated with a lower likelihood of having depressive symptoms (OR per 1-SD LMI = 0.76, 95% CI 0.64-0.91). Participants with an above average FMI more frequently (mean [%], 95% CI) had non-melancholic depressive symptoms (14.7, 11.8-17.7) as compared to those with low FMI (9.7, 7.6-11.9; p = 0.008) regardless of LMI levels. There was no difference between the body composition groups in the likelihood of having melancholic depressive symptoms. The non-melancholic group had higher (mean [kg/m2], SD) FMI (9.6, 4.1) than either of the other groups (BDI < 10: 7.7, 3.1; melancholic: 7.9, 3.6; p < 0.001), and a higher (mean [mmol/l], SD) 2-h glucose concentration (7.21, 1.65) than the non-depressed group (6.71, 1.70; p = 0.005). As hypothesized, non-melancholic depressive symptoms are most closely related to high fat mass index and dysfunctional glucose metabolism.